E-Banking acceptance in Thailand: An emphasis on Islamic banks' customers - Echchabi, Abdelghani (European Journal of Islamic Finance, 2018)
The objective of the paper is to examine the level of acceptance of E-banking services in Thailand, with a special focus on Islamic banks' customers. The study also attempts to identify the main dimensions that would contribute to the acceptance and proper usage of E-banking services by Islamic banks' customers. A survey questionnaire was distributed to 500 Islamic banks' customers in Thailand. The survey covered the capital city of Bangkok and surrounding areas, but focused mostly on the southern part of Thailand, which is majority Muslim area. The collected data was subsequently analysed using descriptive statistics, one sample t-test, and structural equation modelling (SEM). The findings revealed that the Islamic banks' customers in Thailand have a high tendency of adopting E-banking services across-groups. Furthermore, the results showed that perceived ease of use has a significant positive impact on perceived usefulness. In addition, both perceived ease of use and usefulness have a significant positive impact on customers' adoption of E-banking services. These findings have a significant contribution to the theory, policymakers, as well as the practitioners and regulators in the banking and Islamic banking areas.